2016
DOI: 10.1270/jsbbs.15124
|View full text |Cite
|
Sign up to set email alerts
|

Effective marker alleles associated with type 2 resistance to Fusarium head blight infection in fields

Abstract: Molecular markers associated with known quantitative trait loci (QTLs) for type 2 resistance to Fusarium head blight (FHB) in bi-parental mapping population usually have more than two alleles in breeding populations. Therefore, understanding the association of each allele with FHB response is particularly important to marker-assisted enhancement of FHB resistance. In this paper, we evaluated FHB severities of 192 wheat accessions including landraces and commercial varieties in three field growing seasons, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…However, it is often questionable whether markers can be validated in a diverse background to enhance the visibility of the QTL mapping results. Nonetheless, Li et al (2016a) observed very few markers (~3%) holding reproducible marker-trait association while testing 364 genome-wide informative SSR and sequence-tagged site (STS) markers associated with type II FHB resistance. Additionally, Petersen et al (2017) found that only one QTL ( Qfhb.nc-2B.1 ) and its associated marker contributed resistance to disease severity and FDK and was identified as the best candidate for use in MAS among twelve genomic loci identified from diverse wheat nurseries.…”
Section: Genetics Of Fhb Resistance and Breeding Strategiesmentioning
confidence: 99%
“…However, it is often questionable whether markers can be validated in a diverse background to enhance the visibility of the QTL mapping results. Nonetheless, Li et al (2016a) observed very few markers (~3%) holding reproducible marker-trait association while testing 364 genome-wide informative SSR and sequence-tagged site (STS) markers associated with type II FHB resistance. Additionally, Petersen et al (2017) found that only one QTL ( Qfhb.nc-2B.1 ) and its associated marker contributed resistance to disease severity and FDK and was identified as the best candidate for use in MAS among twelve genomic loci identified from diverse wheat nurseries.…”
Section: Genetics Of Fhb Resistance and Breeding Strategiesmentioning
confidence: 99%
“…The average percentage of symptomatic spikelets (PSS) was calculated as the measure of FHB severity. All tested accessions were classified into four classes based on FHB severity, resistant (0 < PSS ≤25%), moderately resistant (25% < PSS ≤50%), moderately susceptible (50% < PSS ≤75%) and susceptible (75% < PSS ≤ 100%) [51].…”
Section: Phenotypingmentioning
confidence: 99%
“…Previous GWAS studies have identified genetic loci controlling FHB (e.g., Wang et al 2017) and awning (e.g., DeWitt et al 2019) (for further examples, see also Discussion). As a complementary approach to the use of high-density genotyping approaches, the availability of genetic markers diagnostic or highly predictive of allelic state at genetic loci controlling major agronomic traits in wheat (e.g., those listed on CerealsDB, https:// www.cerealsdb.uk.net/cerealgenomics/, and subsequently published by Rasheed et al 2016) allow known loci to be rapidly characterized in breeder-relevant germplasm, including association mapping panels (e.g., Li et al 2016). Despite the potential for such marker-informed approaches, relatively limited genome-wide genotypic investigation of Brazilian wheat germplasm has been undertaken to date (Schuster et al 2009).…”
mentioning
confidence: 99%